Paradigm shift of respiratory viruses causing lower respiratory tract infection in children during COVID-19 pandemic in India - Mannat Kang; Subhabrata Sarkar; Suresh Kumar Angurana; Pankaj Singh; Meenakshi Rana; Ishani Bora; Rishi Chetanya; Bharatendu Singh; Jayashree Muralidharan; Radha Kanta Ratho (Journal of Infection in Developing Countries)
Introduction: Acute lower respiratory tract infections (ALRTIs) are the commonest cause of mortality in children mostly attributed to respiratory viruses. During the coronavirus disease 2019 (COVID-19) pandemic, the dynamics and transmission of infections changed worldwide due to widespread public health measures. This study aimed to understand the pattern of respiratory viruses associated with ALRTIs in children pre and during COVID-19 pandemic in India.